Claims of employment discrimination and worker voice. Issue 2 (26th April 2017) - Bender, Keith A.; Heywood, John S.; Kidd, Michael P.
Abstract: Using the U.S. National Study of the Changing Workforce survey, we show that claims of racial and gender discrimination emerge less frequently in workplaces with established worker voice mechanisms. This result accords with the hypothesis that participation enhances perceptions of workplace fairness. We show that while having a supervisor of the same race or gender is associated with reduced discrimination claims, the role of voice tends to be larger when the race or gender of the supervisor is different from that of the worker. This suggests that voice may be particularly important in heterogeneous workplaces.